2010
DOI: 10.1590/s1982-56762010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Phyllody Phytoplasma infecting Sesame (Sesamum indicum) in Myanmar

Abstract: Phyllody symptoms in sesame plants consisting of green leaf-like floral organs were collected from Yezin area, NayPyiTaw Division, Myanmar in January, 2010 and the etiological agent was investigated. By using Polymerase Chain Reaction (PCR), phytoplasma was detected from the symptoms and termed sesame phyllody phytoplasma (SP-MYAN). Restriction Fragment Length Polymorphism (RFLP) analysis of 16S rDNA products revealed that the diseased sesames were infected by phytoplasma belonging to the group 16SrI and subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
(18 reference statements)
0
12
0
2
Order By: Relevance
“…P. aurantifolia' (Akhtar et al 2010;Saqib et al 2006;Wilson et al 2001). The study here and by Win et al (2010) revealed that sesame plant in Myanmar is associated with two phytoplasma species, 'Ca. P. asteris' (AB558132, Win et al 2010) and 'Ca.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…P. aurantifolia' (Akhtar et al 2010;Saqib et al 2006;Wilson et al 2001). The study here and by Win et al (2010) revealed that sesame plant in Myanmar is associated with two phytoplasma species, 'Ca. P. asteris' (AB558132, Win et al 2010) and 'Ca.…”
mentioning
confidence: 59%
“…The study here and by Win et al (2010) revealed that sesame plant in Myanmar is associated with two phytoplasma species, 'Ca. P. asteris' (AB558132, Win et al 2010) and 'Ca. P. aurantifolia' (in this study).…”
mentioning
confidence: 59%
“…Sesame plants affected by phytoplasma showed symptoms of floral virescence, phyllody, stem fasciation, shortened internodes and cracking of seed capsules (Figure j). Sesame phyllody has been reported to be caused by different groups of phytoplasma, that is group 16SrI in India (Khan, Raj, & Snehi, ), Myanmar (Win, Back, & Jung, ) and South Korea (Lee et al., ); group 16SrII in India (Pamei & Makandar, ), Iran (Esmailzadeh‐Hosseini, Mirzaie, Jafari‐Nodooshan, & Rahimian, ), Oman (Al‐Sakeiti, Al‐Subhi, Al‐Saady, & Deadman, ), Pakistan (Akhtar et al., ), Taiwann (Tseng, Deng, Chang, Huang, & Jan, ), Thailand (Martini et al., ) and Turkey (Ikten et al., ); group 16SrVI in Turkey (Sertkaya, Martini, Musetti, & Osler, ); group 16SrIX in Iran (Salehi, Heydarnejad, & Izadpanah, ) and Turkey (Catal, Ikten, Yol, Ustun, & Uzun, ); and subgroup 16SrIX–C in Turkey (Ikten et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of diseased pot marigold were phyllody and proliferation (Figure 2h, Sesame plants affected by phytoplasma showed symptoms of floral virescence, phyllody, stem fasciation, shortened internodes and cracking of seed capsules (Figure 2j). Sesame phyllody has been reported to be caused by different groups of phytoplasma, that is group 16SrI in India (Khan, Raj, & Snehi, 2007), Myanmar (Win, Back, & Jung, 2010) and South Korea (Lee et al, 2004); group 16SrII…”
Section: Discussionmentioning
confidence: 99%
“…P. asteris' (sesame phyllody-SP; AB558132) (Win et al 2010) and 'Ca. P. aurantifolia' (sunn hemp witches' broom-ShWB; AB558143) (Win et al 2011).…”
mentioning
confidence: 99%